A Bifunctional B,N-Based Asymmetric Catalytic Nitrostyrene-Michael Addition Acting through a 10-Membered Ring Cyclic Transition State - ERDEM, SAFİYE (WILEY-V C H VERLAG GMBH, 2022)
The B,N-bifunctional catalyst homoboroproline has been applied to a catalytic asymmetric nitroalkene-Michael addition to beta-nitrostyrene analogues, showing broad substrate tolerance, high conversions and moderate to good asymmetric induction. The ability of homoboroproline to act as an efficient catalyst based on enamine-formation of the secondary amine, coupled with intramolecular Lewis-acid chelation of the nitro function, in a non-FLP manner, to effect efficient and enantioselective catalysis via a proposed large 10-membered ring transition state is remarkable and reinforced by theoretical calculations.
Keywords: amino-boronic acid; asymmetric synthesis; B; N-bifunctional catalysis; homoboroproline; Michael addition; nitroalkenes; HIGHLY ENANTIOSELECTIVE SYNTHESIS; ORGANOBORON COMPOUNDS; DENSITY FUNCTIONALS; ACID; AMINE; ORGANOCATALYSTS; BORYLATION; MECHANISM; KETONES; DERIVATIVES